Developing a user-centred system for long-term elephant monitoring - Fishlock, Vicki; Michelmore-Root, Fran; Njiraini, Norah; Sayialel, Catherine; Moss, Cynthia; Lee, Phyllis (Pachyderm, 2022)
Originally envisaged as a three-year project, the Amboseli Elephant Research Project (AERP) has proved a labour of love for a small, dedicated team who have followed the life trajectories of more than 3,900 individual elephants over five decades. AERP’s unique knowledge base is derived from tracking individually recognized animals in a small well-protected population studied continuously since 1972, providing an important baseline for a free-ranging elephant population with an intact age structure. This dataset forms the basis of our demographic analyses (Moss 2001; Lee et al. 2013), and through training, research, books and films has contributed to global understanding of elephant reproductive biology and behaviour; musth: (Poole and Moss 1981; Poole 1987: Poole 1989; Hollister-Smith et al. 2007); oestrus: (Moss 1983); mothering and grandmothering: (Lee et al. 2016; Lee et al. 2022), elephant cognition: (McComb et al. 2001; Bates et al. 2008; McComb et al. 2014) and communication: (Poole et al. 1988; McComb et al. 2000; McComb et al. 2003). How can we now, after a half century of effort, make our data accessible and of continued use to the global elephant community? To try to answer this demand, AERP has moved beyond a simple relational database into a data management system that allows users to add, map, inspect, edit, and extract data. Here we share some of the key concepts that drove this process and outline our hopes for making elements of the system available to other projects that may benefit from similar capacities.